Underweight and normal weight central obesity among filipinos and its association with cardiovascular risks and diseases. (14th October 2021) - Toledano, B; Vilela, G
Abstract: Introduction: Underweight (UW) and normal weight with central obesity (NWCO) groups are either underrepresented, excluded or merged to the normal weight category in data analysis of epidemiological studies. Purpose: This is a local study conducted that explored the association of underweight versus normal weight central obesity in terms of cardiovascular risks and diseases among Filipinos. Methods: The participants were Filipinos age 20 years old above who had participated and completed the desired data in the National Nutrition Survey II. The participants were categorized into the following groups: underweight (<18.5kg.m 2 ) and normal weight with central obesity (WC ≥80cm or WHR ≥0.85 for females, WC ≥90cm or WHR ≥0.90 for males). This study compared the baseline profile of UW versus NWCO and determined its association with cardiovascular risks and diseases while using adjustment models for age and sex. Results: A total of 3, 009 participants were included in this study, 684 (22.7%) UW and 2, 325 (77.3%) NWCO. The mean age was UW 47.8 versus NWCO 43.2, females 56.6% versus males 43.4%. In comparison to NWCO using adjustment models for age and sex, the ORs for hypertension (OR=1.498, 95% CI 1.23–1.82, p=.001), diabetes (OR=1.71, 95% CI 1.1–2.72, p=.023) and dyslipidemia (OR=1.8, 95% CI 1.5–2.16, p=.0001). Using age stratified model, CAD 25thP (31 years old) OR= 2, 95%Cl 1.5, 2.6 p<.001), 50thP (43 years old), (OR=2.4, 95% CI 1.9, 2.9, p<.001), 75thP (55 years old) (OR=1.9 95% CI 1.6, 2.4 P<.001), CVA 75thP (OR=2.5, 95% CI 1.1, 5.6, p=.021), PAD 50thP (OR=3.4, 95% CI 1.1, 10.7, p=.03). Hypertension 25thP (OR=2.0, 95%Cl 1.5, 2.6 p<.001), 50thP (OR=2.4, 95%Cl 1.9, 2.9 p<.001), 75thP (OR=1.9, 95%Cl 1.6, 2.4 p<.001), Diabetes 25thP (OR=6.7, 95% CI 2.8, 15.9, p<.001), 75thP (OR=1.7, 95% CI 1.1, 2.5, p=.005) and Dyslipidemia 25thP (OR=1.2, 95%Cl, 1.1, 1.6 p=.02) were significantly higher in UW. Conclusion: Lipid and blood pressure parameters differed among male and female UW. A greater association in hypertension and coronary artery disease in all age groups, stroke among the older age group, and diabetes among the younger and older age group is seen among UW versus NWCO among Filipinos. FUNDunding Acknowledgement: Type of funding sources: None.